2011
DOI: 10.1016/j.molimm.2011.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of TLR4 and TLR2/6 coordinates an additive augmentation on IL-6 gene transcription via p38MAPK pathway in U937 mononuclear cells

Abstract: Studies have demonstrated that TLR4 and TLR2 expression by monocytes and the blood levels of TLR4 and TLR2 ligand in diabetic patients are significantly incased compared to nondiabetic patients, indicating that more monocytes in diabetic patients may have coactivation of TLR4 and TLR2. Although it has been shown that either TLR4 or TLR2 activation leads to increased expression of proinflammatory cytokines, the effect of coactivation of TLR2 and TLR4 in mononuclear cells on proinflammatory cytokine expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…Furthermore, we confirmed that HKSA-induced TLR2 overexpression in keratinocytes is related to transcription factors, including p38, NF B, and ERK (MAPK1, MAPK3). In agreement with our study, it has been shown that TLR-2 activation induces IL-6 gene transcription through p38 and NF B signaling [17]. Previous studies have revealed that EGFR signaling restricts allergen-induced IL-6 production in an acute AD model [4], and EGFR acts as a negative regulator of TLR2 induction via p38 MAPK [18].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we confirmed that HKSA-induced TLR2 overexpression in keratinocytes is related to transcription factors, including p38, NF B, and ERK (MAPK1, MAPK3). In agreement with our study, it has been shown that TLR-2 activation induces IL-6 gene transcription through p38 and NF B signaling [17]. Previous studies have revealed that EGFR signaling restricts allergen-induced IL-6 production in an acute AD model [4], and EGFR acts as a negative regulator of TLR2 induction via p38 MAPK [18].…”
Section: Discussionsupporting
confidence: 92%
“…HMGB1 was shown to rapidly interact with TLR2 and TLR4 exposed by RAW macrophage-like cells in one study [36], but not in the other study [29]. RAGE has been demonstrated to play only a minor role in macrophage activation by HMGB1 [15], [37]. Our previous study also showed that pre-incubation of KCs with anti-RAGE antibody and recombinant mouse RAGE/Fc chimera both failed to decrease HMGB1-induced TNF-α and IL-1β production [data not shown], implying that the majority of KCs activation by HMGB1 was independent of RAGE.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study has demonstrated that cAMP/PKA system inhibits SERT activity in intestinal epithelial cells by post-translational regulation [27], which may confirm the involvement of cAMP/PKA in TLR2 short-term effect. Finally, p38 MAPK pathway, which has been demonstrated to mediate TLR2 activity in different cell types [44, 45], was analyzed. The results have shown that p38 MAPK seemed to mediate TLR2/1 and TLR2/6 effect on SERT at both short and long-term treatment.…”
Section: Discussionmentioning
confidence: 99%